Selected list of books and journals for the small medical library. - Brandon, A N (1997)
The introduction to this revised list (seventeenth version) of 610 books and 141 journals addresses the origin, three decades ago, of the "Selected List of Books and Journals for the Small Medical Library," and the accomplishments of the late Alfred N. Brandon in helping health sciences librarians, and especially hospital librarians, to envision what collection development and a library collection are all about. This list is intended as a selection guide for the small or medium-size library in a hospital or similar facility. More realistically, it can function as a core collection for a library consortium. Books and journals are categorized by subject; the book list is followed by an author/editor index, and the subject list of journals by an alphabetical title listing. Due to continuing requests from librarians, a "minimal core" book collection consisting of 78 titles has been pulled out from the 200 asterisked (*) initial-purchase books and marked with daggers ([symbol: see text]). To purchase the entire collection of books and to pay for 1997 journal subscriptions would require $101,700. The cost of only the asterisked items, books and journals, totals $43,100. The "minimal core" book collection costs $12,600.